Мolecular mechanism of Diels-Alder reaction between cyclopentadiene and E-2-arylnitroethenes in the light of DFT computational study - Socha, Jan; Jasiński, Radomir; Barański, Andrzej (Видавництво Львівської політехніки, 2011)
The mechanism of the Diels-Alder reaction between cyclopentadiene and E-2-arylnitroethenes were examined using the B3LYP/6-31G(d) (PCM) algorithm. It was found, that on both, competition paths, the reaction proceeds according to a one-step mechanism.
Keywords: Diels-Alder reaction; nitroalkenes; cyclopentadiene; B3LYP/6-31G(d) calculation; mechanism